2018
DOI: 10.3329/jbcbm.v4i2.39851
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring of seasonal variation of some trace metals concentration in surface water collected from the coastal area of Bangladesh

Abstract: This study was conducted to determine the seasonal variation of Cr, Ni, Cu, Zn, As, Cd and Pb concentrations in water from four coastal sites of Bangladesh. The mean concentrations of trace metals in the water samples in the range of each elements were µg/l) in winter. The mean concentrations of the metals in water followed a decreasing order of Zn > Cu > Pb > Ni > Cr > As > Cd in the summer and Zn > Ni > Cr > Cu >Pb > As > Cd in the winter. The water of Cox's Bazar hatchery site showed the highest levels of Z… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…The average value of salinity recorded 22.02±0.28ppt during pre-monsoon and 30.4±0.69 during post monsoon. Previous study on seasonal variation of physicalchemical parameters in Bakkhali River revealed salinity level 12 ppt in pre monsoon and 27 ppt in post monsoon (Raknuzzaman et al, 2018). The studied results higher than Masoud et al (2019) revealed the values of salinity in the Reju Khal river estuary ranged from 8.0±3.0 to 29.0±0.6 ppt, and Zinat et al (2023) recorded the values of salinity ranged between 5.35±0.10 to 18.82±0.11 in the Passur river as Bakkhali estuary comprised salt marsh sediment and.…”
Section: Physico-chemical Parameters Of Watermentioning
confidence: 93%
“…The average value of salinity recorded 22.02±0.28ppt during pre-monsoon and 30.4±0.69 during post monsoon. Previous study on seasonal variation of physicalchemical parameters in Bakkhali River revealed salinity level 12 ppt in pre monsoon and 27 ppt in post monsoon (Raknuzzaman et al, 2018). The studied results higher than Masoud et al (2019) revealed the values of salinity in the Reju Khal river estuary ranged from 8.0±3.0 to 29.0±0.6 ppt, and Zinat et al (2023) recorded the values of salinity ranged between 5.35±0.10 to 18.82±0.11 in the Passur river as Bakkhali estuary comprised salt marsh sediment and.…”
Section: Physico-chemical Parameters Of Watermentioning
confidence: 93%